Foreign Experience in the Legal Governance of Investment Activities - V. A. Kachalyan (Московский журнал международного права, 2025)
INTRODUCTION. One of the catalysts of the development of the European investment fund industry has been the inception of the undertakings for collective investment in transferable securities (UCITS), the number of which currently exceeds 35,000 funds, who manage assets worth more than 9,5 trillion euros. UCITS are central to the European investment market with their substantive impact on the European economy having been evident for several decades. The identification of the legal factors contributing to the high efficacy level of these undertakings constitutes the primary objective of the research. To achieve this goal, the following tasks shall be addressed: 1) to examine the legal framework governing the activities of UCITS schemes at various stages of its development, so as to estimate the fundamental rules underpinning their operations; 2) to determine the specifics of the functioning of the collective investment vehicles under consideration in terms of modern legislation.MATERIALS AND METHODS. Apart from general scientific methods (analysis, synthesis, induction, deduction, etc.), the specific methods employed within the research are as follows: historical-legal, formal-legal and technical legal methods, which determined the logical structure, content and scientific integrity of this article. The assessment of legislation, other legal acts of EU institutions, white papers, so as official documents of CESR and ESMA presented below is based on Russian and foreign doctrine, mainly in terms of categorization of various types of UCITS schemes.RESEARCH RESULTS. The most significant findings of the research are summarized hereinbefore. 1. The European Union has implemented a comprehensive compendium of rules governing the activities of UCITS. 2. Conditions ensuring fair competition among UCITS at the EU level, as well as between these schemes and different types of funds operating in the US have been 3. Effective and uniform protection of investors has been provided. 4. Restrictions imposed on the free movement of UCITS within the EU have been eliminated.DISCUSSION AND CONCLUSIONS. The legal framework for UCITS funds, which embodies a comprehensive set of rules, is continuously evolving. The high level of maturity of the regulatory framework for UCITS is determined not only by their significance to the European economy, but also because the collective investment schemes, in general, raise capital from retail investors. It requires additional safeguards to protect the latter’s rights and interests.